Pembaruan Hukum Keluarga Islam dalam Masa Berkabung Suami: Tinjauan Kompilasi Hukum Islam dan Konteks Sosial Budaya di Kabupaten Bone: Reform of Islamic Family Law During the Mourning Period for Husbands: A Review of the Compilation of Islamic Law and the Socio-Cultural Context in Bone Regency - Faizal; Rusdaya Basri; Zainal Said (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2025)
This study aims to examine how the people of Bone Regency understand and implement the husband's mourning period as stipulated in the Compilation of Islamic Law (KHI) within their socio-cultural context, and to explore relevant Islamic legal reforms related to this practice. Employing qualitative methods with normative, juridical, and sociological approaches, data were collected through observation, interviews, and documentation. The findings reveal that most residents perceive the husband's mourning period in accordance with the KHI as compatible with local cultural values, particularly emphasizing siri’ (a sense of shame) and pesse (empathy). However, some community members remain unaware of these legal provisions. The implementation aligns well with Bone’s customs and traditions but is gradually evolving due to modernization and technological influences. Furthermore, the theory of ‘urf (customary law) effectively bridges Islamic family law and local culture, demonstrating that Islamic law is dynamic and capable of constructive dialogue with socio-cultural realities. This study highlights the importance of cultural context in interpreting and applying Islamic legal provisions, particularly regarding family law and mourning practices.